The aggravation of mitochondrial dysfunction in nonalcoholic fatty liver disease accompanied with type 2 diabetes mellitus. (September 2015) - Liu, Xiaolin; Zhang, Jingyi; Ming, Yanan; Chen, Xiaoyu; Zeng, Minde; Mao, Yimin
Abstract Objective. Nonalcoholic fatty liver disease (NAFLD) is a mitochondrial disease associated with the metabolic syndrome, but few data are available on the mitochondrial dysfunction of NAFLD after the development of type 2 diabetes mellitus (T2DM). We aimed to identify the changes of mitochondrial function in rat livers when T2DM develops after NAFLD. Material and methods. Rat models of nonalcoholic fatty liver (NAFL) and T2DM were established using high-fat diet and streptozocin. Mitochondria were isolated from the livers. The levels of reactive oxygen species (ROS) and mRNA and protein levels of mitochondrial complex IV (COX IV) and carnitine palmitoyltransferase-1 (CPT-1) were assessed in rat livers. The mitochondrial membrane potential (MP), and the enzyme activities of COX IV and CPT-1 were measured in isolated mitochondria. Results. There were increased ROS, decreased mitochondrial MP, and reduced COX IV and CPT-1 activity in the NAFL and T2DM groups compared with controls (p < 0.05). Compared with NAFL, the T2DM group had higher ROS levels and lower enzyme activity (p < 0.05), but showed no difference in mitochondrial MP. Although COX IV and CPT-1 expression levels in liver decreased in NAFL and T2DM, there was no significant difference between two groups. Conclusion. This study first identified progressively impaired mitochondrial respiratory chain and β-oxidation in NAFLD when T2DM develops, inducing overproduction of ROS, and finally triggering a vicious circle that leads to the aggravation of mitochondrial dysfunction in NAFLD after development of T2DM.